A Construction of High Performance Quasicyclic LDPC Codes: A Combinatoric Design Approach. (3rd February 2019) - Asif, Muhammad; Zhou, Wuyang; Ajmal, Muhammad; Akhtar, Zain ul Abiden; Khan, Nauman Ali
Abstract : This correspondence presents a construction of quasicyclic (QC) low-density parity-check (LDPC) codes based on a special type of combinatorial designs known as block disjoint difference families (BDDFs). The proposed construction of QC-LDPC codes gives parity-check matrices with column weight three and Tanner graphs having a girth lower-bounded by 6. The proposed QC-LDPC codes provide an excellent performance with iterative decoding over an additive white Gaussian-noise( A W G N ) channel. Performance analysis shows that the proposed short and moderate length QC-LDPC codes perform as well as their competitors in the lower signal-to-noise ratio (SNR) region but outperform in the higher SNR region. Also, the codes constructed are quasicyclic in nature, so the encoding can be done with simple shift-register circuits with linear complexity.